Partial and total iodide organification defect in different sibships in a kindred. - Perez-Cuvit, E (1977)
Identical twins with goiter but without intellectual retardation and with slightly delayed bone age were found to have defective iodide organification as demonstrated by incomplete perchlorate discharge tests. They are grandnieces of a normal member of a sibship which included four children with severe retardation and complete thyroid iodide organification defect. The parents and grandparents are not consanguine. Possible explanations are considered for the problem of why the disorder is manifest completely in one sibship and only partially in the other.